2015
DOI: 10.1007/s00109-015-1322-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone replacement therapy regulates microRNA-29a and targets involved in insulin resistance

Abstract: Replacement of growth hormone (GH) in patients suffering from GH deficiency (GHD) offers clinical benefits on body composition, exercise capacity, and skeletal integrity. However, GH replacement therapy (GHRT) is also associated with insulin resistance, but the mechanisms are incompletely understood. We demonstrate that in GH-deficient mice (growth hormone-releasing hormone receptor (Ghrhr)lit/lit), insulin resistance after GHRT involves the upregulation of the extracellular matrix (ECM) and the downregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Lumican, an extracellular matrix protein (ECM), and ECM1 promote collagen fibril organisation and tissue repair, and play a key role in the control of growth factor signalling 46 . Abnormal ECM remodelling has been linked to obesity and insulin resistance, and animal studies provide now evidence that insulin resistance after GH administration in mice involves the upregulation of the extracellular matrix in muscle 47 . There are no studies investigating the effect of growth hormone administration on circulating lumican and ECM1 from the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Lumican, an extracellular matrix protein (ECM), and ECM1 promote collagen fibril organisation and tissue repair, and play a key role in the control of growth factor signalling 46 . Abnormal ECM remodelling has been linked to obesity and insulin resistance, and animal studies provide now evidence that insulin resistance after GH administration in mice involves the upregulation of the extracellular matrix in muscle 47 . There are no studies investigating the effect of growth hormone administration on circulating lumican and ECM1 from the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Staverska et al demonstrated that GHD children are a heterogeneous group as regards the differences in the metabolic profile, probably due to the different IGF-1 bioavailability, and concluded that naïve GHD children have a worse metabolic profile when the IGF-1 bioavailability and the body mass were greater, although the authors do not fully explain this phenomenon ( 54 ). In addition, the role of microRNAs expression in skeletal muscles has been hypothesized as a mechanism that contributes to increased insulin resistance during GHT ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs belong to a clan for non-coding RNAs with 20–24 nucleotides in length ( 14 ). The expression of multiple genes involving various pathways can be regulated coordinately by a singular miRNA, and therefore the gene regulation can be unraveled by discovering changed miRNA expression in complex diseases.…”
Section: Discussionmentioning
confidence: 99%